Aplikasi Museum House of Sampoerna Berbasis Android - Eunice Jesselyn Rudijanto; Andreas Handojo; Anita Nathania Purbowo (Jurnal Infra, 2018)
Museum is a place that has a lot of historical relics and cultural elements, but every museum has a challenge to determine the best way to present the information to visitors. Group of visitors usually get have events and places that have been scheduled by House of Sampoerna’s museum guide, ultimately limiting each individuals to explore deeper on the objects that are more interesting for individuals. In addition, information about objects contained in the museum is limited to the tags or information printed on the area around the object so information can be added.Through this Android-based applications visitors can get information not only in the form of text, but also can be audio and video about objects in the museum that can be accessed individually. In addition, the author added the game mode quiz and guess silhouette by utilizing QR code technology to provide innovation so that museum visitors can further explore museums.The results of the application has two modules, Android-based mobile applications for users or museum visitors and website applications for the museum admin. In the mobile user application there are several menus, there are displaying the detail data of the museum, displaying the list of events contained in the museums, perform a barcode scan process to obtain more complete information, and do the game in the museum. For website applications on the admin museum can manage all the museum data that will be used in the user application. From the test of mobile applications that have been done, 80% of respondents rate this application is good and all respondents rate this application can help if they want to explore the museum alone. While testing the museum admin has satisfied with the website application features.